CONCERNING THE LATEST PLAYS BY CHEKHOV IN CATALONIA - AMIRAGHYAN, HASMIK (Bulletin of Yerevan University H: Russian Philology, 2019)
The paper refers to the constant presence of the plays by Anton Chekhov on the stages of Catalonia, presenting in this context the latest versions by now: Vanya by stage director Alex Rigola (2017-2018) and The Cherry Orchard in Ernesto Caballero’s version (2019). Besides the analysis of these two plays presented by theater companies from Madrid during their tours in Barcelona, the paper also refers to the respective articles in the Catalan press. The critics mainly emphasize the continuing relevance of the questions set out in Chekhov’s plays till the date, as well as the new approaches of the stage directors, which do not receive a unanimous positive feedback in case of The Cherry Orchard and get an unexceptional high evaluation of critics in case of Vanya.